HUBUNGAN RASIO KOLESTEROL TOTAL TERHADAP HIGH DENSITY LIPOPROTEIN DENGAN KEJADIAN SINDROM KORONER AKUT DI RSUD DR. M. HAULUSSY AMBON TAHUN 2018-2019 - Nurul H D J F Ahmad; Irwan Irwan; Eka Astuty; Zulkarnain Zulkarnain; Indrawanti Kusadhiani; Is Ikhsan Hataul (Fakultas Kedokteran Universitas Pattimura, 2021)
Cardiovascular disease is one of the leading causes of death in the world. The primary cause of death in cardiovascular disease around the worldis acute coronary syndrome (ACS). Based on data from the World Health Organization (WHO) in 2015, cardiovascular disease causes 17.5 million deaths or about 31% of all deaths globally, and due to acute coronary syndrome is 7.4 million. This disease is estimated to reach 23.3 million deathsby 2030. ACS is an emergency heart disease that occurs due to rupture or erosion of the atherosclerotic plaque in the coronary arteries. The ratio of total cholesterol to high density lipoprotein (HDL) cholesterol or also known as the Cardiac Risk Ratio is a comparative number that can be used to detect the risk of developing ACS.The purpose of this study was to determine the relationship between the ratio of total cholesterol to high density lipoprotein and the incidence of ACS in RSUD dr. M. Haulussy Ambon in 2018-2019. This research was an observational analytic study with a cross sectional design. Using total sampling method there were 80 peoples included to the sample. The instrument used was medical record data. Datas were analyzed using the SPSS application with the chi square test. Theresult showed p=0,032 (p<0,05). Based on the data analysis, there wassignificant relationship between theratio of total cholesterol to high density lipoprotein (HDL) and the incidenceof acute coronary syndrome in RSUD dr.M. Haulussy Ambon in 2018-2019